Project Approach to Implementation of Interdisciplinary Content of Education at School - A. P. Sukhodimtseva; M. G. Sergeyeva; N. L. Sokolova (Научный диалог, 2017)
The implementation of interdisciplinary content of education at school in the aspect of project approach is discussed. It is noted that this approach is one of effective methodological approaches in pedagogy to ensure students’ achieving the interdisciplinary result of the educational program in accordance with Federal state educational standards of general education (FSES GE). The necessity of using the project approach is stated, together with a systemically-active, which is the methodological basis of FSES GE. The urgency is determined by, on the one hand, the necessity to solve the tasks of the state educational policy reflected in FSES GE and the Professional standard of the teacher of general education. On the other hand, in educational practice there are problems of implementing interdisciplinary content of education at school (both didactic and methodological) in developing interdisciplinary skills of high school students. The authors recommend to use the project approach in two aspects: the pedagogical projecting the educational process of students in a series of subjects of social and humanitarian education and in providing project content of students’ activities. Moreover, educational projecting is considered at the level of project competence of a teacher, while activity of students - in the categories of the educational project. This is the novelty of the approach to the task of implementation of the interdisciplinary content of education at school.